KONSEP SYARI’AH DAN FIQH DALAM KAJIAN EPISTEMOLOGI HUKUM ISLAM - Ma'sum Anshori (STAIN Bengkalis, 2019)
The concept of Islammic legal epistemology both syari’ah and fiqh frequently regarded as uncompleted yet concept, such in its disorder usage among them. Thus this research aimed to search and to explain these surely concepts both syri’ah and fiqh in the establishing process of Islamic legal. Thus, to gain the correct conception of both, the method used in this work is library research with analisys content. The result of research shows that both syari’ah and fiqh has epistemologically distinguished in its position of trilogy Islamic doctrine, Islam, iman, and ihsan. Besides that, both terms constituted not similar, where syari’ah regarded as the origin, the pure, the only devine, and the uncontaminated with the opinion of human, while fiqh is the contrary of that, not origin, not pure, and contaminated with the opinion of human, based on the efforts of a Thinker (Mujtahid) which not same in their intellectual grade. The position of syari’ah though fiqh is as the base, the controll, and the wisdom. The fiqh can not free of this position of syari’ah, and then fiqh should not establish in a wild and blidn as the result. This distinguished epistemology conception should extend the new opinion in establishing Islamic legal on the earth, and automatically should cut down tha partial view and order fanatism among Islamic community. The last conclution of this research that both Syari’ah and Fiqh in completing legal questions depends on the depth of the understanding though Islamic trilogy doctrine, thus the establishing of it should extend the actual benefit and merciful for the human life on this earth. The result are to make Allah and His Messenger as the Judge, to carry back the objective of the law to His wish, to dissappear the conflict of extreme opinion among Ulama, and to seat Ulama as the heir of His Messenger.___________________Keywords: Syari’ah, Fiqh, and Islammic Legal Epistemology.